Relationship between decision-making inputs and productivity among paddy farmers in Integrated Agriculture Development Areas (IADAs), in Malaysia. - Mohamed Haris, Nur Bahiah; Hamzah, Azimi; Krauss, Steven Eric; Ismail, Ismi Arif (Indonesian Society for Knowledge and Human Development, 2013)
The Malaysian paddy rice industry has always been considered as an industry that produces an important commodity which is the main staple food for the nation. The government, during the Tenth Malaysian Plan (2011-2015) period, set a target for every paddy farmer of 10 mt/ha, to ensure that the availability and accessibility of rice are maintained and sufficient. However, the latest production numbers from 2011 revealed that the average production per farmer from the main granary areas was still only 4.77 mt/ha, while in certain parts of the country - such as in the state of Selangor - farmers achieved up to 12 mt/ha. What is the cause of this disparity in production? Despite similarities in facilities, land area and resources, major differences remain in production. Although a multitude of factors could be relevant to this situation, this study aimed to focus on factors influencing the decisionmaking of farmers in correlation with farmers’ productivity. Nine (9) factors were identified that could contribute towards higher paddy productivity. The findings showed a positive and significant relationship between farmers’ productivity and knowledge about paddy (r = 0.159, p < .01), and a negative relationship with age (r= -0.148, p < .01). Hence, having knowledge about paddy farming and being young were the two factors most highly correlated with higher productivity in paddy. These results are an important first step towards understanding factors that could make the agricultural sector in Malaysia more sustainable by increasing the productivity of paddy farmers and increasing the supply of the national staple food.